PELATIHAN PEMBUATAN PRODUK TURUNAN HASIL OLAHAN MADU DAN BEE POLLEN LEBAH KELULUT PADA KELOMPOK PETERNAK LEBAH MILENIAL DESA TELAGA LANGSAT, TANAH LAUT, KALIMANTAN SELATAN - Wiwin Tyas Istikowati; Sunardi Sunardi; Ratih Afrida Lismana Sari; Enos Tangke Arung; Swandari Paramita; Julinda Romauli Manullang; Dimas Fajar Nugroho; Muhammad Rizky Romadhon (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
This community service activity was motivated by the significant potential for developing honey and bee pollen businesses from stingless bees (Trigona sp.) in Telaga Langsat Village, Tanah Laut Regency, South Kalimantan. Although the stingless bee population is quite abundant and millennial breeders have been active in cultivation, utilization of the harvest is still limited to the sale of raw honey with low economic value. Therefore, this activity aims to increase the added value of products through training in the manufacture of processed honey and bee pollen derivative products, such as honey jam. The implementation method included socialization, technical demonstrations, and direct practical assistance with a participatory approach. Evaluation was carried out through observation of participant skills, satisfaction questionnaires, and product feasibility tests. The results of the activity showed an 85% increase in participants' knowledge and skills, and the production of processed product prototypes ready for commercial development. This activity successfully fostered entrepreneurial motivation among young breeders and opened up opportunities for local economic development based on stingless bee farming products.